Finite Element Analysis on Bending of Thin Walled Channel Section Beams of Shallow Open Sections - Sivakumar, Dhar Malingam; Tan, Chee Fai; Abu Bakar, Abdul Hamid; AA, Mokthar; Sanjay, C (2005)
The use of cold-formed sections has increased in recent years from last two decades, with a trend towards using thinner plates in construction, offshore engineering, bridge construction, building construction and naval architecture. They are also extensively used in the manufacture of automobiles, road and rail transport, aircraft, ships, storage systems as well as in many types of offices, industrial applications, agriculture, electrical appliances as well as in domestic appliances. Three types of bucklings are possible for a thin-walled beam of shallow open section subjected to bending. The first type is overall flexural buckling followed by local or plate buckling and finally lateral- torsional buckling. This paper examines the behaviour of thin walled channel section beams loaded in such a way that the bending elements are unstiffened that is they are connected to the adjacent elements on one edge only with the other edge free. This paper does a comparative analysis by using the actual experimental investigations and finite element analysis.